Driving biology: The effect of standardized wound management on wound biomarker profiles. Issue 3 (March 2020) - Dente, Christopher John; Styrmisdottir, Edda; Shi, Audrey; Schobel, Seth; Khatri, Vivek; Potter, Benjamin K.; Forsberg, Jonathan A.; Buchman, Timothy; Kirk, Allan D.; Elster, Eric
Abstract : BACKGROUND: The timing of coverage of an open wound is based on heavily on clinical gestalt. DoD's Surgical Critical Care Initiative created a clinical decision support tool that predicts wound closure success using clinical and biomarker data. The military uses a regimented protocol consisting of serial washouts and debridements. While decisions around wound closure in civilian centers are subject to the same clinical parameters, preclosure wound management is, generally, much more variable. We hypothesized that the variability in management would affect local biomarker expression within these patients. METHODS: We compared data from 116 wounds in 73 military patients (MP) to similar data from 88 wounds in 78 civilian patients (CP). We used Wilcoxon rank-sum tests to assess concentrations of 32 individual biomarkers taken from wound effluent. Along with differences in the debridement frequency, we focused on these local biomarkers in MP and CP at both the first washout and the washout performed just prior to attempted closure. RESULTS: On average, CP waited longer from the time of injury to closure (21.9 days, vs. 11.6 days, p < 0.0001) but had a similar number of washouts (3.86 vs. 3.44, p = 0.52). When comparing the wound effluent between the two populations, they had marked biochemical differences both when comparing the results at the first washout and at the time of closure. However, in a subset of civilian patients whose average number of days between washouts was never more than 72 hours, these differences ceased to be significant for most variables. CONCLUSION: There were significant differences in the baseline biochemical makeup of wounds in the CP and MP. These differences could be eliminated if both were treated under similar wound care paradigms. Variations in therapy affect not only outcomes but also the actual biochemical makeup of wounds. LEVEL OF EVIDENCE: Therapeutic, level IV.